Handbook of Families in the Arab Gulf States: Book Review - Fauzzan Abdurrohman; Raihan Ahmad Ash-Shidiq (Presscience, 2026)
The book entitled “Handbook of Families in the Arab Gulf States” written by Md Mizanur Rahman et al. (2025) is an academic literature that presents a comprehensive discussion on family law studies to understand the dynamics of social life in the Arab Gulf region (GCC) namely Saudi Arabia, the United Arab Emirates, Qatar, Kuwait, Oman, and Bahrain which are undergoing massive social, economic, and cultural transformations due to the currents of globalization and the demands of modernization. The author thoroughly examines changes in family structures, communication patterns, educational frameworks, and marital trends resulting from modern demands. Furthermore, the author highlights the role of women within the family (gender dynamics), patriarchal culture, and divorce. The author posits that state legal policies and technological advancements significantly contribute to shaping family life in the region. Concurrently, migrant families also influence parenting practices and cross-cultural relations within a nation.This book utilizes a scientific approach drawing upon auxiliary disciplines, including sociology, anthropology, psychology, economics, politics, and law. The objective of this book is to provide a comprehensive understanding of how family life in the Gulf states is undergoing massive shifts driven by globalization and modernization. Additionally, it aims to offer deep insights into the role of the family in society, serving as both an object and a subject of change. Within the context of family law, this book examines family law studies from sociological and anthropological perspectives.